ADAPTASI SOSIAL MAHASISWA BARU PENDIDIKAN SOSIOLOGI ANGKATAN 2018 DI FKIP UNIVERSITAS TANJUNGPURA PONTIANAK - Haq, Azizah Nurul; Fatmawati, Fatmawati; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis is "Social Adaptation of New Students of Sociology Education 2018 in FKIP Tanjungpura University Pontianak". The general problem of this research was how the social adaptation of new students in 2018 sociology education in FKIP Tanjungpura University Pontianak. with sub-problems how the social adaptation of new Sociology Education students toward social values, social norms and social control in the environment of FKIP Tanjungpura University Pontianak. This research used descriptive methods in qualitative form. The tools of collecting data were observation guidelines, interview guidelines and documentation studies. . The results of the study showed that (1) the social values seen from the ethical values and spiritual values of new students in the campus environment have been applied by students. This is proven by rules, discipline and spiritual activities which carried out by new students. (2) social norms were seen from the aspect of the role of academic norms, the role of lectures and the role of the daily interactions of new students that have never been separated from the three aspects of the norm and have been running well and implemented well. 3) social control through preventive and repressive actions has been committed by the management of the compilation and lecturers in the form of direction and reprimand. This were directly evidenced by the compilation manager and lecturers who gave oral reprimand and gave punishment to the new students who were not obey the rule.Â Keywords:Â  Social Adaptation, New Students